Conjunctival ultraviolet autofluorescence as a measure of past sun exposure in children - Sun, C; Pezic, A; Mackey, D; Carlin, J; Kemp, A; Ellis, J; Cameron, F; Rodda, C; Dwyer, T; Coroneo, M; Ponsonby, A (American Association for Cancer Research, 2017)
Background Conjunctival ultraviolet autofluorescence (CUVAF) area detected from UVAF photographs is a recently developed potential marker for past sun exposure but its relationship with sun-related factors have not been fully investigated. Methods The study included 339 ethnically diverse and healthy children aged 5-15 years in Melbourne, Australia. Data were collected by questionnaire and examination at school. CUVAF area was measured using a computer programme and analysed as a continuous and dichotomous outcome (any/none). Results The mean age (SD) of the study population was 9.6 (2.7) years with 45.4% males. 53 children (15.6%) had detectable CUVAF and the youngest age at which a child showed sun damage was 8 years. Compared with silicone skin cast score, there was good inter-grader agreement on grading of a random selection of UVAF photographs, with Cohen's kappa 0.85 [95% confidence interval (CI), 0.65-1.00] for total CUVAF area using both eye photographs. Perfect intra-grader agreement was achieved. Fairer pigmentation including medium/fair skin colour [adjusted odds ratio (AOR), 3.42; 95% CI, 1.02-11.48 versus dark/olive] and blue/grey eye colour (AOR, 4.07; 1.73-9.55 versus brown) were associated with increased odds of CUVAF. Increasing lifetime sunburn number (e.g., AOR, 2.89; 1.14-7.35 and 4.29; 1.04- 17.76 for sunburns 2-4 and ≥ 5 times, respectively, versus no sunburns, trend P=0.004) and freckling by the end of last summer were associated with increased odds of CUVAF. Conclusions and impact CUVAF area can be an a priori objective measure of past sun exposure in paediatric populations for future research.